Sensory qualities of mango slices dried by combined convection and vacuum dryer (2001)
This paper presents the sensory characteristics of dried mango slices as affected by the combined use of vacuum dryer and convection dryer: Analysis of Variance (ANOVA) was used in the following manners: Complete Randomized Design (CRD) with three publications and Duncan's Multiples Range Test (DMRT) at 5% level of significance. Drying curve showed that the six hours convection drying and six hours vacuum drying of mango, percent moisture loss was faster resulting in shortest time of drying. Results showed that vacuum drying had a great effect on drying rate for water volatilizes at a lower temperature at reduced pressure. Taste, texture and general acceptability evaluation means showed non-significant differences among the treatments. On the other hand, appearance evaluation mean showed significant differences between the treatments. Combined vacuum and convection drying resulted in significantly shorter time of drying and the same superior quality. Results of this study opened the door for new designs of more efficient dryers for mango and most probably other fruits.
Keywords: Mango -- Preservation; Mango, Dried